Managing haemorrhoids - Nisar, Pasha J (BMJ Group, 2003)
Increased understanding of the anatomy of haemorrhoids has led to the development of new procedures to treat them. Among the surgical options for intractable prolapsed haemorrhoids, formal haemorrhoidectomy now competes with stapled haemorrhoidopexy, which is less painful and allows a shorter convalescence but may have a higher recurrence rate and needs further long term evaluation